A scientometric study on prevalence of gastrointestinal parasites in pigs (Sus scrofa) of India - Krishnamoorthy, P; LAKSHMI, H K; SIJU, S J; SURESH, K P; SHOME, B R (The Indian Journal of Animal Sciences, 2022)
In this study, prevalence of the gastrointestinal (GI) parasites in pigs from India was estimated by employing scientometrics. The prevalence studies on the GI parasites of pigs (n=21) were acquired from online and offline databases (timeline: 2010-2021) and meta-analysis was performed using meta package in R-software. The prevalence of GI parasites in pigs was 54% (95% level: CI 39-69%, PI 5-96% of 8,921 samples tested) in India. A higherprevalence of 81% was reported in 2010 than the recent years (2016-21). The highest prevalence in South zone (78%), and least in West zone (35%) was observed. The prevalence of GI parasites was highest in Tamil Nadu (96%) and lowest in Maharashtra (28%). The higher prevalence was observed in protozoa (30%) than other parasite classes and lower in cestodes (4%) in pigs. More number of studies have been reported on nematode parasites indicating its importance in pigs. A higher prevalence was observed in the studies conducted on samples (84%) collected from slaughterhouse than the faecal samples (46%) in pigs. Among the parasite species, coccidia (29%) were most commonly reported whereas Globocephalus urosubulatus (0.7%) was observed sporadically low. Amongst nematodes and trematodes, a higher prevalence in Ascaris spp. (27%) and Amphistomes (12%), correspondingly was observed. The high GI parasites prevalence zones, states, parasite classes, sample types and parasite species recognized will assist the stakeholders and decision makers, in control and preventive approaches. Further, this study provides the baseline information on GI parasites prevalence in pigs of India for devising effective deworming strategies which ultimately lead to beneficial piggery in India.